2014
DOI: 10.1103/physrevlett.113.120405
|View full text |Cite|
|
Sign up to set email alerts
|

Test of Time Dilation Using StoredLi+Ions as Clocks at Relativistic Speed

Abstract: We present the concluding result from an Ives-Stilwell-type time dilation experiment using 7Li+ ions confined at a velocity of β=v/c=0.338 in the storage ring ESR at Darmstadt. A Λ-type three-level system within the hyperfine structure of the 7Li+3S1 →3P2 line is driven by two laser beams aligned parallel and antiparallel relative to the ion beam. The lasers' Doppler shifted frequencies required for resonance are measured with an accuracy of <4×10(-9) using optical-optical double resonance spectroscopy. This a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 50 publications
(53 reference statements)
2
40
0
Order By: Relevance
“…With a fixed frequency, antiparallel laser beam resonant with one of the legs of the Λ while scanning the second parallel laser beam over the second leg, fluorescence is observed only when both lasers are resonant with the same ions at the center β 0 of the velocity distribution. In this case, Doppler absorption equations (47A) and (47B) are modified as, (49A) and (49B), we get; = (50) Botermann, et al (2014) have confirmed that equations (48) and (50) have been experimentally verified with high accuracy at β=0.338 thereby validating the Doppler absorption equations (42) and (47). It is a matter of historical misinterpretation that such sophisticated experiments are being regarded as verification of Time dilation or Lorentz Invariance, instead of verification of Doppler absorption equations.…”
Section: Tests For Verification Of Doppler Effect For Photonssupporting
confidence: 71%
“…With a fixed frequency, antiparallel laser beam resonant with one of the legs of the Λ while scanning the second parallel laser beam over the second leg, fluorescence is observed only when both lasers are resonant with the same ions at the center β 0 of the velocity distribution. In this case, Doppler absorption equations (47A) and (47B) are modified as, (49A) and (49B), we get; = (50) Botermann, et al (2014) have confirmed that equations (48) and (50) have been experimentally verified with high accuracy at β=0.338 thereby validating the Doppler absorption equations (42) and (47). It is a matter of historical misinterpretation that such sophisticated experiments are being regarded as verification of Time dilation or Lorentz Invariance, instead of verification of Doppler absorption equations.…”
Section: Tests For Verification Of Doppler Effect For Photonssupporting
confidence: 71%
“…Recent precision tests of the relativistic Doppler effect by variants of the Ives and Stilwell experiment considerably improved this bound. Botermann et al (2014) reported that measurements of frequency shifts of hyperfine structure lines of Li + ions moving at speed w/c = 0.3 agree with the relativistic prediction to a few parts in 10 9 . Since they do not report problems with reproduceability as the Earth rotates and moves around the Sun we may take it that their bound in equation (10) bounds the coupling parameter to…”
Section: Tests For Preferred Motionsupporting
confidence: 54%
“…Using precision laser spectroscopy on accelerated atomic beams is a highly sensitive testbed of time dilation due to the motion of an emitting and absorbing quantum object (Gwinner 2005). Using Li + ions as clocks at relativistic speed, the lasers' Doppler shifted resonance frequency was measured with a relative accuracy of < 4 × 10 -9 (Botermann et al 2014) and a constraint on the LLI violating parameter of |α| ≤ 2 × 10 -8 was deduced in this experiment. Only recently, these limits have been overcome by optical clock measurements.…”
Section: Relativistic Redshift Measurements -To Which Level Can We Trmentioning
confidence: 97%